Circulating CD9+/GFAP+/survivin+ exosomes in malignant glioma patients following survivin vaccination - Galbo, Phillip M. (Oncotarget, 2017)
Glioma cells release exosomes in culture and into the extracellular matrix in vivo. These nanobodies transport an array of biomolecules and are capable of mediating cell-cell communication. Circulating exosomes in cancer patients may be indicative of disease status and response to therapy. The inhibitor of apoptosis protein (IAP) survivin (SVN) promotes cancer cell proliferation, local immune suppression and resistance to chemotherapy and it is a potential cancer biomarker. We used imaging flow cytometry to perform quantitative measurements of circulating SVN+ exosomes in the serum of malignant glioma patients undergoing investigational treatment with an anti-survivin vaccine (SurVaxM). Serum from glioma patients contained abundant CD9+ exosomes with both SVN and glial fibrillary acidic protein (GFAP) on their surface. Survivin and GFAP were evaluated both independently and together as possible tumor markers on CD9+ exosomes. Patients with longer time to tumor progression generally exhibited a decrease in circulating CD9+/SVN+ and CD9+/GFAP+/SVN+ exosomes immediately following survivin vaccination; whereas, those with early tumor progression had an increase in exosomes, despite anti-survivin immunotherapy. Serum from non-cancer healthy control individuals had very few detectable CD9+/GFAP+/SVN+ exosomes, although CD9+/GFAP+ exosomes were detectable in small numbers. This study demonstrates that patients with malignant gliomas have CD9+/GFAP+/SVN+ and CD9+/SVN+ exosomes that are released into the circulation and that early reductions in their numbers following anti-survivin immunotherapy might be associated with longer progression-free survival.